2014
DOI: 10.1161/circheartfailure.113.000429
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heart Rate at Hospital Discharge With Mortality and Hospitalizations in Patients With Heart Failure

Abstract: Higher discharge heart rates were associated with greater risk of all-cause and cardiovascular mortality≤1-year follow-up and an elevated risk of 30-day readmission for HF and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
2
28
0
6
Order By: Relevance
“…30 Recently more and more attention is being paid to the problem of hospitalization due to CHF decompensation, which means that identifying factors that affect its occurrence is very important. Reports of found new variables associated with hospitalization have been published, such as heart rate 31 , which was not a factor influencing hospitalization in the present study. This was probably due to the study population undergoing optimal treatment that resulted in satisfactory heart rates.…”
Section: Discussionsupporting
confidence: 42%
“…30 Recently more and more attention is being paid to the problem of hospitalization due to CHF decompensation, which means that identifying factors that affect its occurrence is very important. Reports of found new variables associated with hospitalization have been published, such as heart rate 31 , which was not a factor influencing hospitalization in the present study. This was probably due to the study population undergoing optimal treatment that resulted in satisfactory heart rates.…”
Section: Discussionsupporting
confidence: 42%
“…These data underline again the importance of heart rate control in HF. In patients surviving the acute HF phase, higher heart rate at discharge but not at admission emerged as a potent predictor of 30-day mortality in the study of Habal et al Interestingly, this trend reached significance at heart rates above 90 bpm, a cut-off close to ours [7]. However, the impact of heart rate at admission on in-hospital mortality was not examined in that study.…”
Section: Heart Rate and Outcome In Hfmentioning
confidence: 71%
“…In acute non-arrhythmic HF, little is known about the impact of elevated heart rate on in-hospital outcome [6]. However, higher heart rate at hospital discharge in patients with HF has been associated with greater risk of all-cause and cardiovascular mortality up to 1-year follow-up, and elevated risk of 30-day readmission for HF and cardiovascular disease [7]. The main aim of the present study was to examine the relationship between resting heart rate obtained in survivors 24-36 h after admission for acute non-arrhythmic HF and in-hospital mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This is also a limitation in the present study given that SBP and heart rate at discharge have also been shown to be associated with long-term prognosis. 47, 48 …”
Section: Study Limitationsmentioning
confidence: 99%